Effects of a dietary supplement on inflammatory marker expression in middle-aged and elderly hypertensive patients - Wang, Jia (Clinics (Sao Paulo), 2019)
OBJECTIVES: We aimed to explore the effects of diet on the inflammatory response in middle-aged and elderly people with hypertension. METHODS: Thirty overweight or obese patients with stage one hypertension (age range, 45-75 years) were allocated to either the intervention or control group (n=15 per group; age- and sex-matched). Patients in the intervention group consumed a food powder supplement (100 g) instead of a regular meal. The control group maintained their normal dietary habits. This study lasted for six weeks. Blood pressure, inflammatory marker levels, and energy intake were measured before and after the study. RESULTS: After 6 weeks, the diet composition of the intervention group changed significantly (p<0.05). The intake of proteins, dietary fibre, monounsaturated fat, and polyunsaturated fat increased significantly (p<0.05), while the total energy intake trended towards an increase (p>0.05). In the control group, the total energy intake decreased significantly (p<0.05). The levels of nuclear factor-κB (NF-κB), soluble intercellular adhesion molecule-1 (sICAM-1) and high sensitivity C-reactive protein (hs-CRP) decreased, and adiponectin increased significantly in the intervention group (p<0.05); however, no significant changes were observed in the inflammatory marker levels of the control group. In the intervention group, systolic blood pressure decreased significantly (p<0.05), and diastolic blood pressure also exhibited a decreasing trend. No significant change in blood pressure was observed in the control group. CONCLUSION: The consumption of a food powder supplement can improve diet composition, decrease blood pressure and reduce inflammation in middle-aged and elderly overweight or obese hypertensive patients. The food powder supplement may also have an anti-atherosclerotic effect in hypertensive patients.